Clinical Outcomes After Standard Discectomy and Microdiscectomy for Lumbar Disc Herniation: A Single-Center Study - Mladen Ovcharov (Journal of Biomedical & Clinical Research, 2020)
Unsatisfactory results from lumbar disc herniation (LDH) conservative treatment suggest referral of patients for neurosurgical treatment. The time required for such a decision is considered to be about 4-6 weeks. In most cases, surgery quickly relieves pain symptoms, all along with the restoration of patient functions. The optimal surgical technique for LDH is theoretically controversial. We consider two discectomy methods as quite effective in our clinic: standard open discectomy (SD) and microdiscectomy (MD). Many retrospective studies have demonstrated the superiority of one of these techniques. Most studies describe microdiscectomy as a golden standard for surgical treatment of symptomatic disc herniation. We focused on the clinical aspects and correlations in the surgical treatment of LDH, as presented in the literature.The patients we present were divided by type of surgical procedure (SD or MD), and other parameters: sex, age, duration of symptoms, blood loss, duration of the operation, reoperation rate, Visual Analogue Scale (VAS), and Oswestry Disability Index (ODI). We used chi-square tests (ANOVA analysis) and directional measures to determine statistically significant data. Five hundred eighty-nine single-level lumbar discectomies were performed for five years (2012-2017), and all the patients presented with classical signs of the condition, i.e., vertebral and radicular syndromes. SD was performed on 498 patients, and MD – on 91 patients. Analyses of the parameters mean VAS values of lumbar and leg pain postoperatively, and within one month after surgery demonstrated statistically significant differences between standard and microdiscectomy (p